2022
DOI: 10.1002/admi.202201259
|View full text |Cite
|
Sign up to set email alerts
|

Phosphate Functionalized Ionic Liquid: An Efficient Li+ Migration Inhibitor and Hole Extraction Accelerator for Perovskite Solar Cells

Abstract: There is no doubt that the hole transporting layer (HTL) plays an indispensable role in highly efficient devices. [5] The materials used for HTL include: (1) organic polymer molecules, [6,7] such as poly(3,4ethylenedioxy thiophene):poly(styrene sulfonate) (PEDOT:PSS), poly[bis(4-phenyl) (2,4,6-trimethylphenyl)amine] (PTAA) and poly(3-hexylthiophen-2,5-diyl) (P3HT); (2) inorganic compound, [8] for instance, CuSCN and NiO X . Besides, small molecule HTL materials have been widely studied due to their designabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 40 publications
(64 reference statements)
0
3
0
Order By: Relevance
“…According to a report by Zhu et al, the tiny Li cations are astatic, and thus readily diffuse from the HTL to adjacent layers, such as the perovskite layer and electron transporting layer (ETL), under bias condition or at high temperature as shown in Figure 2E,F 16 . The accumulation of Li cations at the interface between the perovskite and ETL can affect the performance and long‐term stability of the PSCs 38 . More recent reports also have indicated that Li ion‐based byproducts such as LiOH could water‐uptake, and the migration of these Li ions might cause perovskite degradation 39 .…”
Section: Conventional Dopant Systemmentioning
confidence: 98%
See 1 more Smart Citation
“…According to a report by Zhu et al, the tiny Li cations are astatic, and thus readily diffuse from the HTL to adjacent layers, such as the perovskite layer and electron transporting layer (ETL), under bias condition or at high temperature as shown in Figure 2E,F 16 . The accumulation of Li cations at the interface between the perovskite and ETL can affect the performance and long‐term stability of the PSCs 38 . More recent reports also have indicated that Li ion‐based byproducts such as LiOH could water‐uptake, and the migration of these Li ions might cause perovskite degradation 39 .…”
Section: Conventional Dopant Systemmentioning
confidence: 98%
“…16 The accumulation of Li cations at the interface between the perovskite and ETL can affect the performance and long-term stability of the PSCs. 38 More recent reports also have indicated that Li ion-based byproducts such as LiOH could water-uptake, and the migration of these Li ions might cause perovskite degradation. 39 Addressing these limitations of the conventional dopant system, by developing new dopant systems to boost both efficiency and stability, remains a challenging and urgent obstacle to the future commercialization of PSCs.…”
Section: Limitations Of Conventional Litfsi Dopant Systemmentioning
confidence: 99%
“…37 In addition, Noel et al observed that upon applying [BMIM]BF 4 ionic liquid at the SnO 2 /FA 0.83 MA 0.17 Pb(I 0.83 Br 0.17 ) 3 interface, the n-type nature of the perovskite enhances along with other benefits like interfacial defect passivation. 38 In the literature, most of the ionic liquid modifications in perovskite solar cells have been done with imidazolium cation-based ionic liquids, 36–41 which are relatively more hygroscopic. 42,43 On the other hand, quaternary ammonium cation-based ionic liquids have not been explored in perovskite solar cells, which could have potential for interfacial engineering in PSCs.…”
Section: Introductionmentioning
confidence: 99%